UPAYA REMAJA MESJID NURUL IMAN DALAM MENGAKTIFKAN KEGIATAN REMAJA MESJID DI KANAGARIAN GADUT KECAMATAN TILATANG KAMANG KAB AGAM - Zulkifli Zulkifli; Alimir Alimir; Junaidi Junaidi; Jasmienti Jasmienti (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of this research is that the youth mosque is an organization under the auspices of the mosque whose scope of work is to youth who support work programs related to mosques. Mosque youth can provide support and participate in the success of various mosque activity programs which are the responsibility of mosque administrators. However, there are still some mosque youths who have not participated in mosque youth activities and youth activities are still minimal to do such as there are mosque youths who have not prayed in congregation at the mosque, and do not attend mosque youth activities so that the mosque youth activities are reduced. This type of research is qualitative research. The location of this research is the Nurul Iman mosque, Jorong Pandam Gadang Ranggomalai, Kanagarian Gadut, Tilatang Kamang sub-district, Agam district. From the research that has been done, it can be concluded that the efforts of the youth of the Nurul Iman mosque in activating the activities of mosque youth in Kanagarian Gadut, Tilatang Kamang district, as follows provide training, guidance and regeneration of the people, bring in famous outside ustadz, provide interesting book review activities in the area. among mosque youth, holding special mentoring for an-nisa, cooking/tataboga activities for mosque youth, holding training and coaching for the organization of corpses and marasanji for mosque youth. This activity is used by mosque youth for cadre of mosque youth so that they can be useful for themselves, their families and society. Keyword: Nurul Iman Mosque Youth, Mosque Youth Activities